Moskéer i Sverige: En etnologisk studie av omgivningens reaktioner - Karlsson, Pia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1997)
The muslim group in Sweden is, despite its internal heterogenity, now consolidated. This is visualized by, among other things, the building of mosques in a distinct "muslim" style. So far there are only four of these mosques in Sweden, including the Ahmadiyya Chapel in Gothenburg, but building permits have been granted in several other places and more applications are reviewing consideration. To those in the vicinity, the plans cause various reactions charged with varying degrees of emotion. Presented in this article are a number of "themes" that recur in written opposition to mosques not only in Sweden, but also in the rest of Western Europe. In these the mosques are depicted as a threat to e.g. the local environment, democracy and the Swedish/christian cultural heritage. The author of the article discusses whether such expressions should merely be regarded as discursive or if it is possible for an ethnologist to respond also to that which does not immediately present itself as written or oral. Taking both the intimately entwined perspectives into consideration paves the way for a more varied analysis of how reactions to a planned mosque are expressed by people in the environs, and which factors on a local, national and international elvel affect the emergency as well as the shaping of these expressions.